Decisions About Creative Advertising Strategy: Decision-Making Methods and their Applicability - Vasiliauskaitė, Kristina (Ekonomika, 2005)
The article analyzes the creative advertising strategy (hereinafterCAS) decision-making process including the methods used for selection of CAS and the scope of their application. Special attention is devoted to identification and classification of criteria for CAS decision-making. As CAS decisions are made through interaction between the advertising agency and the advertiser, the existing CAS selection methods are evaluated from the perspectives of both subjects of this interaction. The need for accommodation of the two sets of interests is emphasized. The article provides recommendations concerning application of CAS decision-making methods.